Risonanze vichiane nel Saggio sopra gli errori popolari degli antichi di Leopardi. Linee di ricerca sulla credenza. - Rossella GAGLIONE (Laboratorio dell'ISPF, 2018)
[Vichian resonances in Leopardi’s Essay on the popular errors of the ancient people]. This paper aims to show the influence of Vico’s thought in Leopardi’sEssay on the popular errors of the ancient people. Such an influence is evident:in particular, Leopardi resumes Vico’s theory on Truth and the emergence of Belief. There are also differences between the two authors about the criticism they both address to the educational system. Furthermore, both Leopardi and Vico wrote about the cognitive process shared by children and primitive men characterized by wonder and curiosity.